Using microbial responses viewer and a regression approach to assess the eEffect of pH, activity of water and temperature on the survival of campylobacter spp - OMURTAG KORKMAZ, BURCU İREM; İÇEN, HAYRUNİSA (My University, 2022)
This study aimed at developing a model for evaluating the survival of various Campylobacter jejuni strains under different conditions in culture media and poultry data from ComBase. Campylobacter data of culture media (116) and poultry (19) were collected from Microbial Responses Viewer, an additional tool of ComBase. The Weibull equation was selected as a suitable model for the analysis of survival data because of the nonlinearity of survival curves. Then, the fitting parameters (first reduction time and shape parameter) were analysed through a Kruskall-Wallis test and box-whisker plots, thus pointing out the existence of two classes of temperature (0-12 degrees C and 15-25 degrees C) and pH (4-6.5 and 7-7.5) acting on the viability of C. jejuni. Finally, a general regression model was used to build a comprehensive function; all factors were significant, but temperature was the most significant variable, followed by pH and water activity. In addition, desirability and prediction profiles highlighted a negative correlation of the first reduction time with temperature and a positive correlation with pH and water activity.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Food Science; Life Sciences; Campylobacter jejuni; Weibull modelling; predictive microbiology; regression; THERMAL INACTIVATION; LISTERIA-MONOCYTOGENES; RISK-ASSESSMENT; WEIBULL MODEL; JEJUNI; KINETICS; Campylobacter jejuni; Weibull modelling; predictive microbiology; regression